Desenvolvimento de equipamentos e processos de base microalgal e caracterização de bioprodutos de origem fotossintética - Maroneze, Mariana Manzoni (2019)
Microalgae-based processes and products are currently the focus of considerable researchers, government agencies, and private companies around the world due to its wide variety of applications. Due to the high productivities and high lipid content, these microorganisms appear as an important raw material for biofuels production. Microalgae are also considered a potential source of bioactive compounds, especially pigments. However, despite the advantages, the processes based in microalgae still have several challenges that need to be addressed, mainly in terms of culture systems. In this sense, the aims of this work were: (i) understanding microalgae culture systems and their implications; (ii) developing a bench photobioreactor and photoperiod camera; (iii) obtain the technology transfer licensing of the photobioreactor and bench photoperiod camera; (iv) evaluate the influence of photoperiods on photobioreactors; (v) evaluate the influence of photoperiods on microalgal biodiesel production; (vi) determine the presence of esterified carotenoids in cyanobacteria; (vii) determine the carotenoid and chlorophyll profile of the microalgae Chlorella vulgaris, Scenedesmus obliquus, Aphanothece microscopica Nägeli and Phormidium autumnale, relating to the metabolism of these microorganisms. The work developed in this doctoral thesis has shown that although the area of development of microalgae production systems has evolved a lot in the last years, to date, there is no system free from limitations and these are closely related to the contribution of light energy the cells. The developed bioreactor and photoperiod camera deposited at INPI enables studies on lighting strategies in microalgal cultures at laboratory level in the most diverse areas of knowledge. The use of photoperiods has been shown to be an efficient artificial lighting strategy to improve the energy balance of the microalgal biodiesel production process. Three esterified carotenoids were found in the characterization of the carotenoid profile in cyanobacteria, myristoyl-zeinoxanthin and myristoyl-β-cryptoxanthin in A. microscopica Nägeli and mixoxantophyll in P. autumnale. Twenty-nine pigments between carotenoids and chlorophylls were identified in microalgal biomass samples of C. vulgaris, Scenedesmus. obliquus, A. microscopica Nägeli and P. autumnale, using the pepiline methodology. Two carotenoids not yet found in cyanobacteria were found in A. microscopica Nägeli: 5,6-epoxy-β-cryptoxanthin, cis-5,8-furanoid-β-cryptoxanthin and 2'-dehydrodeoxymyxol. A previously unidentified carotenoid was found in the biomass of P. autumnale (Desertifilum), desertixanthin.